Analisis Gaya Bahasa Dalam Lirik Album Lagu Nadin Amizah â€œKalah Bertaruhâ€: Kajian Hermeneutika - zeni rahmah; Maguna Eliastuti; Nurindah Virginia Wigusti Ayu; Ulmi Apriyanti Putri; Habib Muhammad Candra; Fenny Putri Agnes Sibarani (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This study aims to analyze and describe the style of language contained in the song lyrics on the album Kalah Bet by Nadin Amizah. This research is a qualitative research using a qualitative descriptive approach. Data collection techniques performed by the authors are data identification, data analysis, data classification, data description, data interpretation. The results of this study the authors concluded that the lyrics of the song Nadin Amizah use a lot of figurative language such as personification, antithesis, metaphor, hyperbole, simile, anaphora, assonance, allegory, and euphemism. The meaning contained in the three lyrics of the song are: (1) Problems of lovers who believe that their love will have a beautiful ending but it doesn't. (2) Someone who feels down. (3) Someone who leaves his past to pick up a new love.